2020
DOI: 10.1038/s41372-020-00788-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers of bronchopulmonary dysplasia and bronchopulmonary dysplasia-associated pulmonary hypertension

Abstract: Objective To quantify and compare levels of potential biomarkers in neonates with i) Bronchopulmonary dysplasia (BPD); ii) BPD-associated pulmonary hypertension (BPD-PH); iii) PH without BPD; and iv) neonates without lung disease at ~36 weeks postmenstrual age. Study Design Multiple potential biomarkers were measured in plasma samples of 90 patients using a multi-spot enzyme-linked immunosorbent assay. Statistical tests done included one-way ANOVA to compare levels of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…These changes will affect the flow of tissue fluid, aggravate the inflammatory response, and lead to edema, suggesting that lower extremity edema may also be related to increased Ang-2 expression and could be the reason why lower extremity edema and Ang-2 are independent risk factors for DVT. Sahni et al (35) also reported that the serum level of Ang-2 is positively correlated with inflammatory mediators such as TNF-α and interleukin 6, and these two inflammatory factors have been proved to be risk factors for DVT in many studies. As a pro-inflammatory factor, Ang-2 plays an important role in the physiological activities of promoting inflammation and vascular leakage (32).…”
Section: Discussionmentioning
confidence: 98%
“…These changes will affect the flow of tissue fluid, aggravate the inflammatory response, and lead to edema, suggesting that lower extremity edema may also be related to increased Ang-2 expression and could be the reason why lower extremity edema and Ang-2 are independent risk factors for DVT. Sahni et al (35) also reported that the serum level of Ang-2 is positively correlated with inflammatory mediators such as TNF-α and interleukin 6, and these two inflammatory factors have been proved to be risk factors for DVT in many studies. As a pro-inflammatory factor, Ang-2 plays an important role in the physiological activities of promoting inflammation and vascular leakage (32).…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, scientific and technical developments in neonatology have led to a survival rate of <10% to >80% for low birth weight premature infants in developed countries; however, this development has led to the appearance of more morbidities [9][10][11]. The pathogenesis of BPD is multifactorial, oxygen toxicity, barotrauma, volutrauma, and even biotrauma, where IL-1β, IL-6, and IL-8 play a part in the aetiology [12,13]. It is accepted that the frequency increases as the gestational age and the birth weight decrease and the risk, especially at preterms born less than 30 weeks of gestation, is reported to be higher [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, research on biomarkers is of high relevance to improve the diagnostic options in early detection of aberrant organ development. Candidates have been studied in clinical situations of known organ damage, e.g., BDP (294,295) and neonatal kidney injury (296)(297)(298) and will have to be tested in the context of metabolic programming. Importantly, the goal is not to label an individual organ function as pathological beyond classical criteria but to identify individuals who are at risk to develop disease later in life in order to provide targeted prevention strategies.…”
Section: Systemic Consequences Of Fetal Programmingmentioning
confidence: 99%